Implementasi Protokol Cleanliness, Health and Safety (CHS) oleh Pelaku Perjalanan Wisata di Era Pandemi Covid-19 menurut Persepsi Wisatawan - Pusparani, Pusparani; Pradhipta, RMW Agie (Jurnal Ilmiah Pariwisata; Vol 27 No 1 (2022): Jurnal Ilmiah Pariwisata, 2022)
The impact of the Covid-19 pandemic cause the tourism sectors lack of trust from  the tourists, both foreign and domestic tourists. In order the business actors in the tourist sectors can running their economy activity needed the effort to gain confidence  from tourist with give the easing of restrictions on community activities and also the opening of these destinations accompanied with cleanliness, health and safety behaviour in order  do not trigger the emergence of a new wave of the Covid-19 pandemic. The government has formulated a New Normal Adaptation for the lungs of tourism actors. The guidelines for the Cleanliness, Health, Safety (CHS) protocol that have been compiled are expected to be implemented by travel agents. To see how far the implementation of the CHS protocol in the Covid-19 Pandemic era has been carried out by Travel Agents, this research is carried out. The results show that the average value of the highest CHS protocol implementation is carried out by tourists and tourist attractions, which is 92%, followed by accommodation service actors at 80%, eating/drinking service actors at 77% and the last one being transportation service actors at 70%. Keywords : Covid Pandemic, Cleanliness, Health and Safety Protocols